Isospin and energy position of isovector giant multipole resonances - Khvastunov, V.M. (Вопросы атомной науки и техники, 2000)
The energy position Em of the dipole and quadrupole giant resonances versus the nuclear isospin T₀ is discussed. It is shown, that the proposed line E =a+bT₀ is in the better agreement with the experimental data of the dipole giant resonance, then in the case of Goldhaber-Teller and Steinwedel-Jensen models.